Analysis of Cerebrospinal Fluid Flow Quantification though Aqueduct of Sylvius using Phase Contrast Cine MR Imaging - Wonglao, Sarayut (Journal of The Department of Medical Services, 2021)
Background: Neurological institute of Thailand has a high frequency of cerebrospinal fluid (CSF flow) quantification through aqueduct of sylvius so we were performed the difference region of interest (ROI) measurement comparable to standard while doesn’t take a long time of post-processing.Objective: To evaluate compare the results of each ROI measurement and post-processing time to standard.Method: The retrospective study of the 50 patients with and without suspected Normal Pressure Hydrocephalus (NPH) who had 2D Phase Contrast cine MR Imaging with MRI 3T since 2015-2017 from PACS in Radiology Department. The analysis of CSF flow measurement has different ROI measurement include ROI 1 was performed automatic measurement in a circular ROI, manual measurement for ROI 2 that allows to standard, 50%, 75%, 25% manual measurement of the data for the ROI 3, 4, 5 in order and copy contours for the ROI 6. The ANOVA test was used to compare the values obtained each ROI measurement with the SPSS statistical.Results: The values of the ROI 3, 4 and 6 were not statistically significant to the ROI 2 and the ROI 6 was used post-processing time less than other ROI measurement.Conclusion: The ROI 6 was performed comparable precision to standard and shorter post processing time.